2016
DOI: 10.1002/app.43830
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanowire network embedded in polydimethylsiloxane as stretchable, transparent, and conductive substrates

Abstract: Highly stretchable transparent conductors where Ag nanowire networks (AgNWs) are reliably embedded into a polydimethylsiloxane (PDMS) substrate are presented. In spite of the weak physical and chemical interaction between Ag nanowires and PDMS, a significantly high transfer efficiency and uniform embedding of AgNW percolation mesh electrodes into PDMS was achieved by simply coating aerogels onto the AgNWs and using water‐assisted transfer. By the failure‐free transfer and reliable bonding with the substrate, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Ag NW-PDMS [78] Random network, embedded 80 15 90 Ω sq −1 at 70% Aerogels Ag NW/PDMS [79] Random network, 80 14 40% change until 10%…”
Section: Zonyl Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag NW-PDMS [78] Random network, embedded 80 15 90 Ω sq −1 at 70% Aerogels Ag NW/PDMS [79] Random network, 80 14 40% change until 10%…”
Section: Zonyl Surfactantmentioning
confidence: 99%
“…Our group found that Zonyl fluorosurfactant improves the bonding between the NWs and the PDMS matrix, thus enabling the efficient transfer of NWs into PDMS (Figure 3c). [36] Kim et al employed aerogels as a strong transfer medium for embedding Ag NWs into PDMS, [78] which accommodated 70% strain with a resistance increase to 90 Ω sq −1 .…”
Section: Metal Nw-based Stecmentioning
confidence: 99%
“…With technological advances in both flexible and wearable electronics, there are increasing demands for flexible transparent conductors that can endure a wide range of external factors, including mechanical and environmental stresses . Ag‐nanowire‐based electrodes are known to offer a high flexibility and stretchability with good optical and electrical properties; thus, great efforts have been made with respect to the application of Ag nanowires as transparent conductors in flexible and wearable electronic devices . However, flexible substrates used for Ag‐nanowire electrodes are typically susceptible to external mechanical scratches, which may degrade the optical and electrical performances of the devices with these electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their large specific surface area, high porosity, and tunable mechanical properties, nanofibers have broad application in many fields, including bioengineered structures, air and water filtration, electronics, drug delivery, fuel cells, biomedical tissue engineering, building materials, and smart clothing . However, nanofibers produced by traditional methods present some problems, including their toxic solvents and low output.…”
Section: Introductionmentioning
confidence: 99%